Influence of premixed swirl-stabilized flame on the cooling performance of an effusion-cooled combustor liner - Xiang Lu; Yongbin Ji; Bing Ge; Shusheng Zang (Case Studies in Thermal Engineering)
The impact of premixed swirl-stabilized flame on the cooling performance of an effusion-cooled combustor liner perforated by cylindrical and fan-shaped holes is investigated under varying blowing ratios. Infrared technology is employed to ascertain the wall temperature, and computations are performed to elucidate the interaction mechanism between the flame and the cooling jets. The results demonstrate that since the premixed flame has not yet burnt out before impinging on the wall, the mainstream near the wall contains low-temperature mixtures in the swirl impingement zone and high-temperature gas in the corner recirculation and liner tail. Consequently, the wall temperature in the swirl impingement zone is relatively low, while the cooling effectiveness is high. Conversely, the corner circulation zone and the tail of the liner exhibit reduced cooling effectiveness. The increase in the blowing ratios has a negligible influence on the cooling effectiveness distribution but can enhance the cooling effectiveness and its uniformity. The fan-shaped holes are similar in the distribution of cooling effectiveness to the cylindrical ones but higher in value. Meanwhile, they have better uniformity of cooling effectiveness than the cylindrical holes, as more cooling air is assigned to holes in the corner recirculation zone and liner tail where cooling effectiveness is lower.